1990
DOI: 10.1111/j.1365-2621.1990.tb03917.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation at ‐78°C on Microbial Populations in Dairy Products

Abstract: The effect of low temperature ( -78°C) gamma irradiation was investigated on microbial populations in selected dairy products to determine the irradiation dosage needed to produce commercially sterile dairy products for immunosuppressed patients. 40 kGy irradiation was sufficient to sterilize ice cream and frozen yogurt, but not mozzarella or Cheddar cheeses. Up to 8 wk continued incubation of the 40 kGy irradiated products at 7°C or 35°C resulted in no resuscitative growth in ice cream or yogurt, but identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…(1990) reported D 10 values from 3·6 to 4·1 kGy at −78°C in dairy products. These D 10 values are similar to those found in this study, although those reported by Hashisaka et al. 1990 were determined at −78°C.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…(1990) reported D 10 values from 3·6 to 4·1 kGy at −78°C in dairy products. These D 10 values are similar to those found in this study, although those reported by Hashisaka et al. 1990 were determined at −78°C.…”
Section: Discussionsupporting
confidence: 91%
“…Following this same rationale, a radiation dose comparable with a thermal process for canned foods would be 40 kGy using the data from this report, 45 kGy for the Bowen et al. (1996) data, and 49·2 kGy for the highest value reported by Hashisaka et al. (1990).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…40 kGy sono stati sufficienti per la radappertizzazione del gelato e dello yogurt gelato, ma non per la mozzarella e per il formaggio cheddar 30 . 40 kGy sono stati sufficienti per la radappertizzazione del gelato e dello yogurt gelato, ma non per la mozzarella e per il formaggio cheddar 30 .…”
Section: Radappertizzazioneunclassified
“…Due to the characteristics of composition, that is, a high quantity of water and the presence of saturated and unsaturated fats, milk and its derivatives are sensitive to oxidative rancidness after radiation treatment, which in many cases makes the products unacceptable for the consumption because of the presence of unwanted flavor. For this reason, studies using radiation on fluid milk and dairy products have been seldom done, in spite of work having been done in recent decades to examine the efficiency of radiation on the reduction of microorganisms which contaminate and deteriorate fluid milk (Naghmoush et al, 1983;Rosenthal et al, 1983;Schoonmaker, 2001;Searle and Mcathey, 1989), on the chemical-physical and sensory characteristics of irradiated milk (Ciesla, et al, 2004;Guimarães et al, 2005) and on its effects on milk derivatives (Gurgel, 2000;Hashisaka et al, 1990;Pietranera et al, 2003;Silva, 2003). There are at present several methods for detection of rancidity in foodstuffs.…”
Section: Introductionmentioning
confidence: 99%